Organizational Citizenship Behavior of Indonesian Elementary School Teachers: In Altruism Perspective - Safitri, Nurul Annisa; Muhibbin, Ahmad; Narimo, Sabar (Budapest International Research and Critics University, 2022)
So far, there have been many studies that discuss OCB. However, there are still gaps in the discussion of OCB, especially in the perspective of altruism in elementary school teachers. Therefore, the purpose of this study was to describe OCB in elementary school teachers from the perspective of altruism. This research is qualitative research involving elementary school teachers, context in Indonesia. The ethnographic design used answers four main questions, namely: “where do I start looking?”, “how do I find it?”, “how do I recognize that it has found something significant?”, and “how to understand what it is?”. By answering questions, the researcher succeeded in assessing altruism in OCB in elementary school teachers. As a result, OCB teachers in altruism are willing to replace fellow teachers who do not enter, they like to help fellow teachers and are willing to guide new teachers. It is hoped that the results of this study can be used to provide information about OCB which is an exemplary behavior for teachers in elementary schools to have, in an effort to increase the effectiveness of elementary schools.